Mapping the Memories of "Living on Light": Processuality with Actor-network Theory - Raunola, Ilona (Approaching religion, 2024)
In this article a case study of the phenomenon of "living on light" is presented. The interlocutor "Eva" shares her memories from the period when she did not eat material food. Actor-network theory (ANT) is adopted to analyse the interview. This methodological framework sheds light on the connections between interacting human and non-human entities and thus reveals their agency. The phase of living on light appears to Eva as part of her personal spiritual progress. At the same time, relations with the family become ambivalent since Eva does not want to share her true spiritual devotion. Eva's experiences are demonstrated and re-imagined by mapping them with ANT concepts such as "intermediary" and "centre of calculation". Eva's period of living on light is discussed in three different forms of processuality. Characteristic of both the phenomenon of living on light and of ANT reading is the renovative quality of the ongoing processuality.